STUDENTS’ PERCEPTION OF THE USE OF TED TALK VIDEOS IN PUBLIC SPEAKING CLASSS - Istiqlaliah Nurul Hidayati; Shafira Cahyani (Fakultas Komunikasi, Sastra, dan Bahasa, 2022)
TED Talk videos contain speakers discussing the latest thinking about education, learning, innovation, etc. The videos are made as learning media in a public speaking class. This research investigates students’ perceptions of the use of TED Talks video in public speaking class. There were tirty five students contributing as participants of this research. To gain the research data, the researcher used three research instruments: questionnaire, students and lecturer interviews. According to the data analysis, it was found that both the students and lecturer in public speaking have similar perceptions of the use of TED Talk videos. It can be inferred that the use of TED Talk videos can enhance the students’ speaking performance and give new information to them. It is recommended that EFL classes can use TED Talk videos as authentic learning media.